Blood pressure estimation using the pulse oximeter - Chan, Jonathan Mai Zheng (Nanyang Technological University, 2020)
With the increasing need of better healthcare in the current world, essential health parameters for diagnosis requires a higher degree of efficiency to be delivered. Various methodologies of measurement are used in monitoring across all levels, from homes to hospitals. An example of parameter measurement will be on the human blood pressure, and the theoretical aspect of this parameter is the Windkessel model, which will then be further explained in the literature review. The goals of this project will be the study on the complexity of the 4-element modified Windkessel Model and the development of computational application to achieve validation and accuracy of the theoretical model.